Acute effects of air pollution on the incidence of hand, foot, and mouth disease in Wuhan, China. (15th March 2020) - Yang, Zhiyi; Hao, Jiayuan; Huang, Shuqiong; Yang, Wenwen; Zhu, Zhongmin; Tian, Liqiao; Lu, Yuanan; Xiang, Hao; Liu, Suyang
Abstract: Previous studies have shown that exposure to ambient air pollution is associated with hand, foot, and mouth disease (HFMD), but the results are limited. Our study aimed to investigate the effects of several major air pollutants on HFMD in the warm and cold seasons in central China. A Poisson Generalized additive model (GAM) was used to assess the association between short-term exposure to ambient air pollution and the incidence of HFMD at Wuhan, China during 20152016. Daily cases of HFMD were extracted from the infectious disease surveillance systems of Hubei provincial center for disease control and prevention (Hubei CDC). Data on air pollution, including sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), ground-level ozone (O3 ), particulate matter (PM) with an aerodynamic diameter less than or equal to 10 μm (PM10 ), and PM with an aerodynamic diameter less than or equal to 2.5 μm (PM2.5 ) were obtained from 10 national air quality monitoring stations in Wuhan. We found that the association between air pollution and HFMD was most pronounced at lag days 10 and 11. The results of the single-pollutant model show that the associations of SO2, NO2, O3, PM10, and PM2.5 with HFMD were all statistically significant. The results of the multi-pollutant model showed that NO2, O3, PM10, and PM2.5 are reduced after excluding the confounding of co-pollutants. The seasonal analysis showed that the effect of air pollution in the cold season was higher than in the warm season. Our research provides more evidence related to air pollution and HFMD, and helps policy makers to develop regulations for the prevention and control of the disease. Graphical abstract: Image 1 Highlights: All pollutants are significantly associated with HFMD at lag 10 - 11. Air pollution have a stronger effect on HFMD in the cold season. The effects of NO2, O3, and PM are reduced in the multi-pollutant models.